The Lawyer- Client Relationship: Part Three: Fee Arbitration - Hunter, Richard J.; Shannon, John H. (Advances in Social Sciences Research Journal, 2022)
This article discusses issues relating to a conflict between a lawyer and his or her client concerning legal fees. The article is Part III in a series considering issues that arise during the course of the lawyer-client relationship. The authors argue that the Mandatory Fee Arbitration Act of 1977, enacted in the State of California, should serve as a model for all states in order to resolve such conflicts extrajudicially—outside of the normal legal process of filing a lawsuit in a civil court of competent jurisdiction over such matters. The Mandatory Fee Arbitration system, abbreviated MFA, is an important “risk management” tool in jurisdictions that adopt this approach. Unless otherwise noted, this article is based on an analysis of the California Act, pursuant to the provisions of California Business and Professions Code (Bacon, 2020). The article also provides a comprehensive list of resources available to both lawyers and their clients in case should a fee dispute arise [Appendix I]. In Appendix II, the authors provide a comprehensive list of state and/or local bar association lawyer-client fee arbitration systems for future research.